Hostile intent ebook - Eason, Lynette (Danger Never Sleeps, 2021)
FBI Special Agent Caden Denning is part of the task force assigned to catch a serial killer targeting military families—only he needs Ava Jackson's help to do so. When the killer turns his sights on Ava, the investigation turns into a fight to survive.